Knowledge of medical students on organ donation and transplantation - Batista, Carla Reale (2010)
Purpose: To assess knowledge of medical students on organ donation and transplantation, the concept of brain death, and their ability in identifying contrary factors to the organ and tissue donation. Methods: This is a cross-sectional study conducted with 266 medical students from the first to fourth grades of the Medical school. Data collection was conducted between August and October 2010. We have applied a questionnaire containing demographic data and 13 multiple choice questions on the subject. Results: Among respondents, 61.3% had educational activities on organ transplantation during the Medical course. Sixty percent of students ranked their knowledge on the topic as regular. Eighty-eight percent of students understood the concept of brain death, and 72% had notions about the diagnosis. When asked about what organs can be transplanted in case of living donors, 78.9% answered correctly. As to transplants performed under no heartbeating, 45.4% answered the question, and 53.4% was not aware of them. When asked on the intention to donate organs and tissues, 78.6% were donors, and the analysis per semester showed a progressive increase in the willingness to donate. As to the intensive care for the maintenance of potential organ donors, 75.5% of students were unaware on the supportive measures required. Regarding to the communication to the family about the death of a relative, 50.4% knew how to make such approach. Conclusion: We concluded that the majority of medical students in the sampling studied had knowledge on brain death. During the medical course, students increase their knowledge about transplantation and donation of organs and tissues. This knowledge increases the intention to donate, suggesting that education is essential to improve rates of organ donation. Thus, it is necessary to insert specific matters or courses on the organ and tissue transplants in the medical school curriculum